Antioxidant Activity of Laportea decumana (Roxb) Wedd Ethanol and n-Hexane Extracts - Thalib, Abdul; Masadah, Rina; Prihartono, Prihartono; Hamid, Firdaus; Haidir, Muhammad; Hasan, Hulan; Keliwawa, Sudin; Labulawa, Irman (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Laportea decumana (robx.) wedd. is a traditional medicine used by Indonesian people, especially in eastern Indonesia, Maluku Ambon. But its utilization has not been based on evidence-based research, so it still needs to be developed to be used as complementary nursing therapy in the future. Aim: This study aims to determine the phytochemical content and antioxidant activity of Laportea decumana (robx.) wedd. from Ambon Maluku. Method: Extraction is done by the maceration method with 96% ethanol solvent. Phytochemical tests are performed with thin-layer chromatography (TLC) to look at flavonoids, tannins and triterpenoids, then alkaloids and saponins using tube tests. The antioxidant activity test was conducted using the 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) method. Results: Laportea decumana (robx.) wedd. phytochemical test positively contains alkaloids, flavonoids, tannins, triterpenoids and saponins. The antioxidant activity of Laportea Decumana (Robx) Wedd Ethanol Extract (LDrW-EE) 22.81 ppm, Laportea Decumana (Robx) Wedd n-Hexane Extract (LDrW-NHE) 44.89 ppm and vitamin C 6.03 ppm. Conclusion: LDrW-EE antioxidant activity is better when compared to LDrW-NHE but no better than vitamin C